2014
DOI: 10.1371/journal.pone.0089342
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Human Papillomavirus Type 154 and Tissue Tropism of Gammapapillomaviruses

Abstract: The novel human papillomavirus type 154 (HPV154) was characterized from a wart on the crena ani of a three-year-old boy. It was previously designated as the putative HPV type FADI3 by sequencing of a subgenomic FAP amplicon. We obtained the complete genome by combined methods including rolling circle amplification (RCA), genome walking through an adapted method for detection of integrated papillomavirus sequences by ligation-mediated PCR (DIPS-PCR), long-range PCR, and finally by cloning of four overlapping am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 68 publications
2
28
0
Order By: Relevance
“…Our observations are not surprising since previous studies have demonstrated that typically cutaneous HPV types (Beta-and Gamma-PVs) were relatively common in the mucosal epithelia, suggesting a possible dual tissue tropism of the majority of HPV species [1,13,32,28,45,46]. In addition, two Gamma-PV types were identified in a surface swab of a genital wart and a cervical cancer biopsy sample, possible as part of the normal mucosal microbiota, as reported previously [23,26].…”
Section: Discussionsupporting
confidence: 88%
“…Our observations are not surprising since previous studies have demonstrated that typically cutaneous HPV types (Beta-and Gamma-PVs) were relatively common in the mucosal epithelia, suggesting a possible dual tissue tropism of the majority of HPV species [1,13,32,28,45,46]. In addition, two Gamma-PV types were identified in a surface swab of a genital wart and a cervical cancer biopsy sample, possible as part of the normal mucosal microbiota, as reported previously [23,26].…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, because more than 90% of warts identified in the anogenital region of adult patients are etiologically associated with sexually transmitted HPV6 and HPV11 (11,12,(16)(17)(18)43), when testing this patient population the method of choice in our laboratory is the HPV6/11 RT-PCR (40), followed in the case of a negative result by HPV2/27/57 multiplex RT-PCR and Low-risk Alpha-PV-PCR (31). Alpha-PV-negative wart tissue samples are additionally tested in our laboratory for research purposes only for the presence of several Gamma-and Mu-PVs that cause sporadic cutaneous warts (7,9,11,12,26,44,45). All HPV-negative warts identified in the anogenital region of patients of all ages and both sexes are additionally tested in our laboratory for the presence of molluscum contagiosum virus (MCV) using the MCV FRET RT-PCR (45) because, due to the similar clinical appearance of lesions, up to 10% of molluscum contagiosum lesions can be misdiagnosed as condylomata acuminata or verrucae vulgares and vice versa (45)(46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…HPV154 species γ-11, was first identified by FAP-PCR from a swab of a wart at the intergluteal cleft of a three-year-old boy [67]. The complete genome was obtained by combination of RCA, genome walking through an adapted method for detection of integrated PV sequences by ligation-mediated PCR (DIPS-PCR), long-range PCR and, finally, by cloning of four overlapping amplicons of RCA-amplified material.…”
Section: Hpv154mentioning
confidence: 99%
“…The complete genome was obtained by combination of RCA, genome walking through an adapted method for detection of integrated PV sequences by ligation-mediated PCR (DIPS-PCR), long-range PCR and, finally, by cloning of four overlapping amplicons of RCA-amplified material. HPV154 has been detected in 3% (2/62) of forehead skin swabs from healthy children [67].…”
Section: Hpv154mentioning
confidence: 99%